2019
DOI: 10.1186/s12891-019-2659-0
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous full-endoscopic anterior transcorporeal cervical discectomy and channel repair: a technique note report

Abstract: Background Compared to anterior cervical discectomy and fusion (ACDF), cervical motion segment and disc was retained through anterior transcorporeal herniotomy (ATH). But surgical field and manipulation in traditional ATH was restricted by the narrow channel. Percutaneous full-endoscopic transdiscal cervical discectomy is a minimally invasive and functional spine surgery. However, significant loss of intervertebral disc height was inevitable. This study was done to illustrate the feasibility, safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Combined with the advantages of full-endoscopic technique and anterior transcorporeal approach, PEATCD has acquired good therapeutic effects. However, how to design a bone channel with an appropriate size and proper direction for surgery has not been mentioned in these previous PEATCD reports (16)(17)(18)27,28).…”
Section: E817mentioning
confidence: 99%
“…Combined with the advantages of full-endoscopic technique and anterior transcorporeal approach, PEATCD has acquired good therapeutic effects. However, how to design a bone channel with an appropriate size and proper direction for surgery has not been mentioned in these previous PEATCD reports (16)(17)(18)27,28).…”
Section: E817mentioning
confidence: 99%
“…One study included both anterior and posterior approaches (3.2%) 15 , 20 studies reported a posterior approach (64.5%), 6,7,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and 10 studies reported an anterior approach (32.3%). 14,[34][35][36][37][38][39][40][41][42] All studies involved foraminotomy or discectomy by removing a disk fragment. Only one study reported fusion with an anterior approach using an intervertebral cage and iliac crest graft.…”
Section: Operative Techniquementioning
confidence: 99%
“…Two studies chose the trancorporeal approach. 39,41,43 The endoscopic variant is considered a motion-preserving approach for the cervical spine. It protects the disc from surgical damage.…”
Section: Anterior Endoscopic Cervical Discectomymentioning
confidence: 99%
See 1 more Smart Citation
“…The nal follow-up modi ed MacNab criteria scores were recorded for evaluating the early clinical outcomes. The four grades of the modi ed MacNab criteria are as follows [11]: Excellent: Complete elimination of symptoms, work activities and quality of life returned to the original levels. Good: Mild symptoms, minor activity restrictions without affecting the routine work and quality of life.…”
Section: Clinical Assessmentmentioning
confidence: 99%